ОЦЕНКА КОЛИЧЕСТВА КОПИЙ TREC И KREC У НЕДОНОШЕННЫХ НОВОРОЖДЕННЫХ С РЕСПИРАТОРНЫМ ДИСТРЕСС-СИНДРОМОМ - Полякова, Екатерина Александровна; Гурьянова, Ирина Евгеньевна; Стёганцева, Мария Владимировна; Берестень, Светлана Анатольевна; Старовойтова, Анастасия Сергеевна; Луцкович, Дмитрий Викторович; Белевцев, Михаил Владимирович (FORCIPE, 2022)